2008
DOI: 10.1002/path.2457
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of mammary gland stem cells

Abstract: Emerging evidence from a variety of tissue types, including the mammary gland, suggests that normal stem and progenitor cells are the likely targets for malignant transformation, and that these transformed cells can function as cancer stem cells that drive tumour growth. In order to develop therapies that target these cancer stem cells, it is essential to determine the molecular mechanisms that regulate the growth and differentiation of these cells and their normal counterparts. To this end, a number of quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
154
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(168 citation statements)
references
References 95 publications
5
154
2
4
Order By: Relevance
“…CD14 is a surface protein, which is expressed in monocytes/macrophages (41,42), being often used, in the literature, as a stem cell marker (11). This protein is one of the useful markers used to identify mouse mammary progenitor cells (43). Our results show that the proportion of CD14 1 cells is higher than 60% in the nontumorigenic MCF10-A cell line and less than 15% in the Hs578-T tumorigenic and metastatic cell line.…”
Section: Discussionmentioning
confidence: 70%
“…CD14 is a surface protein, which is expressed in monocytes/macrophages (41,42), being often used, in the literature, as a stem cell marker (11). This protein is one of the useful markers used to identify mouse mammary progenitor cells (43). Our results show that the proportion of CD14 1 cells is higher than 60% in the nontumorigenic MCF10-A cell line and less than 15% in the Hs578-T tumorigenic and metastatic cell line.…”
Section: Discussionmentioning
confidence: 70%
“…Apart from the existence of genetically distinctive non-modal populations, intra-tumour phenotypic diversity can be explained by non-genetic mechanisms, including epigenetic regulation of genes Intra-tumour genetic heterogeneity in breast cancer 563 and molecular networks, epithelial-to-mesenchymal transition, interaction with specific niches and tumour microenvironment [2,[7][8][9][10][11], and by the 'cancer stem cell' hypothesis [12][13][14][15][16]. This hypothesis proposes that the intra-tumour heterogeneity stems from, and is maintained by, a small population of cells (the socalled 'cancer stem cells'), which give rise to more differentiated cells and thus create the phenotypic diversity of tumours [2,12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular and cellular processes in mammospheres are similar as those in developing alveoli of the mammary gland [20]. Hierarchically, mammary cells range from terminally differentiated cells to undifferentiated progenitors and stem cells, the latter two being likely targets for malignant transformations in cancer [21]. It was shown that an entire mammary gland can be reconstituted from a single mammary stem cell [22].…”
Section: D Organization-mammosphere Formationmentioning
confidence: 90%